The role of maternal diet on offspring hyperinsulinaemia and adiposity after birth: a systematic review of randomised controlled trials. (2nd October 2022) - North, Sylvia; Crofts, Catherine; Thoma, Christian; Zinn, Caryn
Abstract: In utero diet may be directly related to the risk of fetal hyperinsulinaemia and offspring metabolic health. This review examines the relationship between maternal dietary exposures and sub-clinical fetal hyperinsulinaemia and neonatal adiposity. Articles were identified in MEDLINE, Web of Science, Cochrane Controlled Register of Controlled Trials, Cumulative Index to Nursing and Allied Health Literature, SCOPUS, and SPORTDiscus (September 2019–March 2021) using the preferred reporting items for systematic reviews and meta-analyses guidelines. PROSPERO registration ID CRD42020146453. Studies were selected by two independent reviewers. Randomised controlled trials (RCT) involving a dietary intervention with pregnant women (healthy pregnancy, gestational diabetes mellitus and obesity) and reporting fetal cord-blood insulin, c-peptide, glucose or adiposity estimates were included. One author extracted all information on main study characteristics and outcomes. Risk of bias was assessed using the Cochrane Collaboration's bias risk assessment tool. A total of 733 articles were identified. Fourteen articles from 11 RCTs (3614 participants) were included. Studies reviewed showed no specific effect of maternal diet on neonatal cord blood insulin, c-peptide or glucose levels. Infants born to mothers who followed a low glycaemic load (GL) had lower skin fold thickness compared to controls. Interventions that provided individualised nutrition counselling to women with obesity or previous infant born > 4 kg were also associated with lower adiposity. The studies reviewed suggest that lifestyle-based dietary interventions to improve glycaemia (low GL) have a protective effect against excess adiposity. Future studies should incorporate multi-modal interventions with dietary counselling to support lifestyle changes throughout gestation and include assessments of maternal insulin resistance at recruitment.